Predictors of breast self-examination practices among female undergraduates in selected tertiary institutions in Ogun State, Nigeria: The Health Belief Model Approach - Fehintola et al. (Rwanda Medical Journal)
INTRODUCTION: The study assessed the knowledge and practices of breast self-examination and predictors among female undergraduates at Olabisi Onabanjo University and Babcock University in Ogun State using the Health Belief Model.